In their own words: a synthesis of the qualitative research on the experiences of adults seeking asylum. A systematic review of qualitative findings in forced migration - Hoare, Thomas; Vidgen, Andrew; Roberts, Neil (Medicine, conflict, and survival, 2017)
Quantitative research indicates that some forced migrants have mental health needs. Asylum seekers are a group of forced migrants applying for asylum status in a host country, and are often subject to rights restrictions and threat of deportation, though little is known about subjective experiences of the asylum journey and process of claiming asylum. The current paper therefore describes a systematic review of the qualitative literature, examining asylum seekers experiences of asylum journey, from country of origin, to arrival and adaptation to host countries. A search of four databases yielded 122 studies. Inclusion/exclusion criteria were applied and 15 studies were retained and critically appraised. The country where research was conducted, study aims, sample characteristics and methodological approaches were all critically reviewed for included studies. Study aims fell into four themes; 'an aspect of the asylum seeker journey'; 'psychological distress and wellbeing'; 'cultural identity and adaptation to new environment' and 'social welfare, employment and housing'. Studies were generally high quality and indicate issues around choice of asylum destination, distress created by uncertainty around asylum decision and hostile reactions of host communities. However, few studies have examined the experiences of asylum seekers specifically, which is important given the unique circumstances of this population.